Validated HPLC method for the standardization of Phyllanthus niruri (herb and commercial extracts) using corilagin as a phytochemical marker - Colombo, Renata [UNESP]; Batista, Andrea N. de L. [UNESP]; Teles, Helder L. [UNESP]; Silva, Geraldo H. [UNESP]; Bomfim, Giovani C. C. [UNESP]; Burgos, Rosilene C. R. [UNESP]; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Pelicia, Clicia R.; Guimaraes, Fabiana M.; Heimberg, Maria Celia H. (John Wiley & Sons Ltd, 2009)
Phyllanthus niruri L., commonly known in Brazil as 'quebra-pedra', has long been used in the treatment of diverse diseases and especially urolithiasis. The therapeutic effects of P. niruri are attributed to various compounds present in the plant, including the hydrolysable tannin corilagin. In the present study, high-performance liquid chromatography (HPLC-/PAD) profiles of leaves and commercial extracts of P. niruri were examined and three compounds, found to be present in all of the samples studied, were isolated by open column chromatography over C,8 silica gel followed by preparative HPLC. These compounds were identified by nuclear magnetic resonance as corilagin, rutin and ethyl 3,4,5-trihydroxybenzoate. Corilagin, which has been proposed as a phytochemical marker for P. niruri, was employed as an external standard in the development and validation of a rapid and efficient qualitative and quantitative HPLC assay for the analyte. The method may be applied in the standardization of herbs and phytomedicines commercialized in Brazil as quebra-pedra. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: Phyllanthus niruri; corilagin; HPLC-PAD; standardization; quebra-pedra